2023
DOI: 10.1186/s13063-023-07083-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N-acetylcysteine on systemic lupus erythematosus disease activity and its associated complications: a randomized double-blind clinical trial study

Abstract: Backgrounds N-acetylcysteine (NAC) has broadly been used as an anti-oxidant agent in various types of diseases. This study aimed to assess the effect of NAC on the systemic lupus erythematosus (SLE) disease activity and outcome. Methods In this randomized, double-blind clinical trial study, 80 SLE patients were recruited that were classified into two groups: 40 patients received NAC (1800 mg/day; 3 times per day with 8-h intervals) for 3 months and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…N-acetylcysteine (NAC) slightly reduces albumin/creatinine ratio and suppresses renal fibrosis in diabetic nephropathy in diabetic rat models (208,209). High-dose NAC decreased SLEDAI scores and BILAG classes significantly in a randomized double-blind clinical trial, though patients with acute flare threatening vital organs were excluded (210). Pre-and post-treatment with NAC in septic rats were protective against kidney injury while long-term administration of NAC worsened organ failure and did not improve albuminuria.…”
Section: Antioxidantsmentioning
confidence: 98%
“…N-acetylcysteine (NAC) slightly reduces albumin/creatinine ratio and suppresses renal fibrosis in diabetic nephropathy in diabetic rat models (208,209). High-dose NAC decreased SLEDAI scores and BILAG classes significantly in a randomized double-blind clinical trial, though patients with acute flare threatening vital organs were excluded (210). Pre-and post-treatment with NAC in septic rats were protective against kidney injury while long-term administration of NAC worsened organ failure and did not improve albuminuria.…”
Section: Antioxidantsmentioning
confidence: 98%
“…Sirolimus is being evaluated in a phase II/III trial in LN (NCT04892212). Along this line, N-acetylcysteine (NAC) improved disease activity in association with reversal of mTOR activation in T cells [46,47]. NAC is being evaluated in a phase II trial in SLE (NCT00775476).…”
Section: T Cellsmentioning
confidence: 99%
“…These vasculo-protective effects were associated with reduced Th17 infiltration. Recently, a randomized double-blind clinical trial study demonstrated that N-acetylcysteine treatment reduced vascular complications in SLE [134]. Idebenone, a synthetic quinone analog of coenzyme Q10, enhances electron transfer chain function by bypassing deficient complex I activity and increasing the amount of ATP synthesized, thereby improving mitochondrial physiology, reducing the aberrant production of mROS, the formation of NETs and the activation of the type I IFN pathway.…”
Section: Metabolic Modulators and Slementioning
confidence: 99%